The European Commission’s Proposal for a Common Consolidated Corporate Tax Base - Fuest, C (2008)
The European Commission is currently preparing a proposal for a directive on the introduction of a common consolidated corporate tax base (CCCTB). This paper reviews the current state of the European Commission's preparation of the CCCTB proposal and discusses the implications for efficiency and fairness of the tax system. The analysis concludes that more evidence of significant economic benefits from introducing a CCCTB would be required to generate widespread support for the project.